Expression of the Corynebacterium glutamicum panD Gene Encoding l-Aspartate-α-Decarboxylase Leads to Pantothenate Overproduction in Escherichia coli - Dusch, Nicole (American Society for Microbiology, 1999)
The Corynebacterium glutamicum panD gene was identified by functional complementation of an Escherichia coli panD mutant strain. Sequence analysis revealed that the coding region of panD comprises 411 bp and specifies a protein of 136 amino acid residues with a deduced molecular mass of 14.1 kDa. A defined C. glutamicum panD mutant completely lacked l-aspartate-α-decarboxylase activity and exhibited β-alanine auxotrophy. The C. glutamicum panD (panD(C.g.)) as well as the E. coli panD (panD(E.c.)) genes were cloned into a bifunctional expression plasmid to allow gene analysis in C. glutamicum as well as in E. coli. The enhanced expression of panD(C.g.) in C. glutamicum resulted in the formation of two distinct proteins in sodium dodecyl sulfate-polyacrylamide gel electrophoresis, leading to the assumption that the panD(C.g.) gene product is proteolytically processed into two subunits. By increased expression of panD(C.g.) in C. glutamicum, the activity of l-aspartate-α-decarboxylase was 288-fold increased, whereas the panD(E.c.) gene resulted only in a 4-fold enhancement. The similar experiment performed in E. coli revealed that panD(C.g.) achieved a 41-fold increase and that panD(E.c.) achieved a 3-fold increase of enzyme activity. The effect of the panD(C.g.) and panD(E.c.) gene expression in E. coli was studied with a view to pantothenate accumulation. Only by expression of the panD(C.g.) gene was sufficient β-alanine produced to abolish its limiting effect on pantothenate production. In cultures expressing the panD(E.c.) gene, the maximal pantothenate production was still dependent on external β-alanine supplementation. The enhanced expression of panD(C.g.) in E. coli yielded the highest amount of pantothenate in the culture medium, with a specific productivity of 140 ng of pantothenate mg (dry weight)(−1) h(−1).